Mastering elastic Kubernetes service on AWS : deploy and manage EKS clusters to support cloud native applications in AWS /: deploy and manage EKS clusters to support cloud native applications in AWS. (2023) - Orr, Malcolm; Cao, Yang-Xin
No abstract available